Cardiac calcium regulation in human induced pluripotent stem cell cardiomyocytes: Implications for disease modeling and maturation - Ernst, Patrick; Bidwell, Philip A.; Dora, Michaela; Thomas, David D.; Kamdar, Forum (Frontiers in Cell and Developmental Biology, 2023)
Human induced pluripotent stem cell cardiomyocytes (hiPSC-CMs) are based on ground-breaking technology that has significantly impacted cardiovascular research. They provide a renewable source of human cardiomyocytes for a variety of applications including in vitro disease modeling and drug toxicity testing. Cardiac calcium regulation plays a critical role in the cardiomyocyte and is often dysregulated in cardiovascular diseases. Due to limited availability of human cardiac tissue, calcium handling and its regulation have most commonly been studied in the context of animal models. hiPSC-CMs can provide unique insights into human physiology and pathophysiology, though a remaining limitation is the relative immaturity of these cells compared to adult cardiomyocytes Therefore, this field is rapidly developing techniques to improve the maturity of hiPSC-CMs, further establishing their place in cardiovascular research. This review briefly covers the basics of cardiomyocyte calcium cycling and hiPSC technology, and will provide a detailed description of our current understanding of calcium in hiPSC-CMs.